Do We Need CO2 Shadow Prices on Public Expenditures? - Andreas Löschel; David Schulze (Wirtschaftsdienst)
Abstract High prices for the emission of climate-damaging greenhouse gases are an efficient way to achieve the shift to a sustainable growth model and chosen climate targets. Despite the introduction of CO2 prices for emissions in Germany and Europe, large sectors are not yet covered by CO2 pricing. In addition, the prices are most likely too low to sufficiently reflect climate damages or to ensure the achievement of the climate targets. Against this background, the introduction of a shadow price on emissions from public procurement and investments is another mechanism that can support the energy transition and may also make indirect emission savings financially attractive. The expected effect is limited by the low price range, the short planning horizon and the current limited application to federal expenditures. Potential hurdles include the legal complexity and the effort required to avoid double burdens should the scope of shadow pricing be extended to state and municipal levels. For financially weak public budgets, a shadow price means an additional burden. They can therefore only be a transitional solution until the introduction of a comprehensive price on greenhouse gas emissions.